The compatibility of prescribing guidelines and the doctor-patient partnership: a primary care mixed-methods study - Solomon, Josie (Royal College of General Practitioners, 2012)
BACKGROUND: UK policy expects health professionals to involve patients in decisions about their care (including medicines use) and, at the same time, to follow prescribing guidelines. The compatibility of these approaches is unclear. AIM: To explore the relationship between prescribing guidelines and patient-partnership by exploring the attitudes of patients, GPs and primary care trust (PCT) prescribing advisors. DESIGN AND SETTING: A mixed-methods study using qualitative, semi-structured interviews followed by a quantitative, questionnaire survey in primary care in Northern England. METHOD: Interviews were conducted with 14 patients taking a statin or a proton pump inhibitor, eight GPs and two prescribing advisors. A multi-variate sampling strategy was used. Qualitative findings were analysed using framework analysis. Questionnaires based on themes derived from the interviews were distributed to 533 patients and 305 GPs of whom 286 (54%) and 142 (43%) responded. RESULTS: Areas of tension between guidelines and patient partnership were identified, including potential damage to trust in the doctor and reduced patient choice, through the introduction of the policy maker as a third stakeholder in prescribing decisions. Other areas of tension related to applying single condition guidelines to patients with multiple illnesses, competition for doctors' time and the perception of cost containment. Many GPs coped with these tensions by adopting a flexible approach or prioritising the doctor–patient relationship over guidelines. CONCLUSION: Rigidly applied guidelines can limit patient choice and may damage the doctor–patient relationship. GPs need flexibility in order to optimise the implementation of prescribing guidelines, while responding to individuals' needs and preferences.